2013
DOI: 10.1016/j.exppara.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to Strongyloides venezuelensis infection is related to the parasite load and absence of major histocompatibility complex (MHC) class II molecules

Abstract: In human and murine models strongyloidiasis induce a Th2 type response. In the current study we investigated the role of different loads of Strongyloides venezuelensis in the immune response raised against the parasite and the participation of the major histocompatibility complex (MHC) class II molecule in the disease outcome in face of the different parasite burden. The C57BL/6 wild type (WT) and MHC II(-/-) mice were individually inoculated by subcutaneous injection with 500 or 3000 S. venezuelensis L3. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…We found that T and B cell-deficient Rag2 -/-mice exhibited a 20-day delay (i.e., requiring 32 days in total) in cessation of S. venezuelensis egg excretion during primary infections and a 25-day delay (i.e., requiring 37 days in total) in the secondary infection (versus no eggs detected during secondary infections in any of the wild-type mice) (Fig. 3A), underscoring the importance of an adaptive immune response for effective secondary immune responses to this nematode (8,11,13,14,41,(46)(47)(48). In addition, we confirmed that the number of adult worms in the intestines on day 8 of the primary infection was significantly higher in the Rag2 -/-mice than in the corresponding wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that T and B cell-deficient Rag2 -/-mice exhibited a 20-day delay (i.e., requiring 32 days in total) in cessation of S. venezuelensis egg excretion during primary infections and a 25-day delay (i.e., requiring 37 days in total) in the secondary infection (versus no eggs detected during secondary infections in any of the wild-type mice) (Fig. 3A), underscoring the importance of an adaptive immune response for effective secondary immune responses to this nematode (8,11,13,14,41,(46)(47)(48). In addition, we confirmed that the number of adult worms in the intestines on day 8 of the primary infection was significantly higher in the Rag2 -/-mice than in the corresponding wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between Strongyloides sp. and the host is generally characterized by the T helper type 2 response (Th2), with consequent cytokine production, eosinophilia and production of antibodies . Although the role of NO in infection by Strongyloides sp.…”
Section: Discussionmentioning
confidence: 99%
“…and the host is generally characterized by the T helper type 2 response (Th2), with consequent cytokine production, eosinophilia and production of antibodies. 9,14 Although the role of NO in infection by Strongyloides sp. is still unknown, there are reports in the literature showing that molecules usually related to the Th1 profile, such as NO, can contribute to the elimination of or resistance to infection by extracellular parasites, such as Giardia lamblia, 34 Entamoeba histolytica, 35 Brugia malayi, 36 Taenia crassiceps 37 and Schistosoma mansoni.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations